COMPARISON OF 2005 SOCIAL STUDIES COURSE CURRICULUM AND 2017 SOCIAL STUDIES COURSE DRAFT CURRICULUM - Bayram TAY (International Journal of Eurasia Social Sciences, 2017)
This study aims to compare the Social studies curriculum of 2005 and the Social studies curriculum draft of 2017. This research is a case study among qualitative research models. We used the technique of document analysis as the sources of our research comprise the Social studies curriculum book of 2005 and the Social studies curriculum draft of 2017 published by the Ministry of National Education. Some results of the research are as follows: While the Social studies curriculum of 2005 had a vision, the Social studies curriculum draft of 2017 has a basic philosophy equivalent to vision; the Social studies curriculum of 2005 was based on a thematic understanding while the Social studies curriculum draft of 2017 is unit-based although it seems to entail a thematic understanding; both include objectives; the Social studies curriculum of 2005 included totally 174 attainments, whereas the Social studies curriculum draft of 2017 include 136 attainments in total. The Social studies curriculum of 2005 was organized within the frame of 9 learning domains in general. The Social studies curriculum draft of 2017 is organized within the frame of 7 learning domains with changes in the names of some domains.